Eficácia do procedimento de suplementação com ferro em ciclos para redução da anemia em pré-escolares - Coutinho, Geraldo Gaspar Paes Leme (2010)
To evaluate the efficacy of iron supplements given at intervals corresponding to the mean life of red blood cells compared to weekly supplementation, in reducing the prevalence of preschool anemia. Method: Ninety-nine children from public day care centers with ages from 24 to 59 months old were randomly divided into two groups. This is a randomized comparative study. All the children received 40 doses of 30 mg of ferrous sulfate during a 10-month intervention period. Group 1 received once weekly supplementation and Group 2 received supplementation in two 5-month cycles, each cycle consisting of one month of supplementation (20 workdays) and four months without supplementation. Results: The prevalence of anemia after the supplementation regimens reduced from 20.20% to 5.05% (p < 0.0005); the reduction was not significantly different between the two groups (p = 0.35). The mean hemoglobin concentration increased in both groups (Group 1: 0.27 g/dL; p < 0.016 and Group 2: 0.47 g/dL; p < 0.0005) without significant differences between the groups (p = 0.17). Conclusions: The two regimens reduced the prevalence of anemia, were low-cost, and with high rate of compliance. The regimen in cycles was evaluated easier to apply than the weekly one.